The novice - Matharu, Taran (Matharu, Taran. Summoner, 2015)
"When blacksmith apprentice Fletcher discovers that he has the ability to summon demons from another world, he travels to Adept Military Academy where must decide where his loyalties lie. The fate of an empire is in his hands"--OCLC.